Factors Influencing Lecturers’ Stress in Online Teaching: Evidence from Higher Education - Ahmad, Kamilah; Idris, Nur Izah Izzati (Research in Management of Technology and Business, 2026)
This study aims to examine the stress-inducing factors among lecturers in online teaching contexts. A quantitative research design was employed using a survey method, with data collected from 117 lecturers at Universiti Tun Hussein Onn Malaysia (UTHM). The data were analysed using the Statistical Package for Social Sciences (SPSS), including descriptive and correlation analyses. The findings indicate that technological difficulties, lack of facilities, facilitating conditions, and student behaviour are all significantly associated with lecturers’ stress levels. Among these factors, technological difficulties (r = 0.393, p < 0.001) and student behaviour (r = 0.391, p < 0.001) were found to have the strongest relationships with stress. The results suggest that challenges related to technology usage and student engagement are the primary contributors to stress in online teaching environments. This study highlights the importance of enhancing institutional support, improving technological infrastructure, and addressing student-related challenges to reduce stress among lecturers. The findings provide practical implications for higher education institutions in developing effective strategies to support lecturers and improve the quality of online teaching.